Analis Keterkaitan Pengakuan Pendapatan Dalam Accrual Method Terhadap Pelaporan Pajak Pertambahan Nilai pada Perusahaan PT. Prima Tata Kargo Palembang - Krisnawati, Ike; Lilianti, Emma; Jusmani, Jusmani (Universitas PGRI Palembang, 2025)
ABSTRACT Indonesia is a developing country where business people support the country's economy. Business people make a significant contribution to the country by paying taxes. Value Added Tax, also known as VAT, is a tax charged on the sale and purchase of goods and services provided by corporate taxpayers or individual taxpayers who have met the requirements as Taxable Entrepreneurs (PKP). The accrual revenue recognition method (also known as the “Accrual Method”) is an accounting method in which revenues and expenses are recognized or recorded when transactions occur rather than when money is received. This is one of the company's accounting policies. Research at PT. Prima Tata Kargo Palembang was motivated by the desire to learn how financial reports are recorded and whether they are based on recognized SAK. PT Prima Tata Kargo Palembang is a company that as a taxpayer has met the Subject and Object requirements of Value Added Tax (VAT) which has been operating in Indonesia for quite a long time with its activities as a company in the field of container loading/unloading services. The purpose of this research is to determine the recognition of income using the accrual method in reporting Value Added Tax at the company PT. Prima Tata Kargo Palembang.The research methodology used in this research is a descriptive method, namely a problem-solving approach that focuses on describing the condition of the subject/object in the research. The research results show that the relationship between value added tax reporting and income at PT. Prima Tata Kargo uses the accrual method, where income is recognized when the transaction occurs so that income is recognized according to the actual situation and the recognition, payment and tax reporting are appropriate for that period. The higher the income recognized from providing services, the higher the value added tax payable and reported by PT. Prima Cargo Management. Calculating value added tax at PT. Prima Tata Kargo is based on the basic tax rate of 11% of the tax base. PT. Prima Tata Kargo has fulfilled its obligations to collect, pay and report tax obligations related to VAT. Keywords: Income Recognition, Accrual Method, Value Added Tax (VAT), Business, Taxable Entrepreneurs. ABSTRAK Indonesia adalah negara berkembang dimana para pelaku bisnis mendukung perekonomian negara. Para pelaku bisnis memberikan kontribusi yang signifikan kepada negara dengan membayar pajak. Pajak Pertambahan Nilai, juga dikenal sebagai PPN merupakan pajak yang dibebankan pada penjualan dan pembelian barang dan jasa yang disediakan oleh wajib pajak badan atau wajib pajak orang pribadi yang telah memenuhi syarat sebagai Pengusaha Kena Pajak (PKP). Metode pengakuan pendapatan akrual (juga dikenal sebagai